Active matter. (22nd May 2017) - Ramaswamy, Sriram
Abstract: The study of systems with sustained energy uptake and dissipation at the scale of the constituent particles is an area of central interest in nonequilibrium statistical physics. Identifying such systems as a distinct category—Active matter—unifies our understanding of autonomous collective movement in the living world and in some surprising inanimate imitations. In this article I present the active matter framework, briefly recall some early work, review our recent results on single-particle and collective behaviour, including experiments on active granular monolayers, and discuss new directions for the future.